Legal Analysis of the Implementation of Collateral Takeover Without Auction in Decision No. 53/PDT.G/2025/PT PTK - Abdul Rahman; Kawakib Kawakib (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
The purpose of this study is to emphasize the principle of prudence in banking contract practices, which is a fundamental principle in resolving problem loans, especially in the execution of collateral by creditors. This study discusses two main points: first, a theoretical review of the principle of prudence, default, agreements, mortgage law, and legal protection for debtors; second, a critical analysis of the legal considerations in Decision No. 53/Pdt.G/2025/PT PTK which authorizes the unilateral takeover of collateral objects by creditors without going through an auction procedure. This study uses a normative juridical method, with an approach to statutory regulations, legal doctrine, and decision studies. The results of the analysis show that the creditor's actions in taking over collateral without an independent appraisal and without an auction are contrary to the principle of prudence, the principle of justice, and consumer protection. The judge's decision in this case focuses too much on the formal legality of ownership and ignores the substantive process to protect the debtor's position as a weaker party in contractual relationships in banking.Tujuan dalam